RESULTS OF THE THIRD MONITORING STAGE OF 137CS ACCUMULATION BY SPECIES OF GRASS-DWARF-SHRUB LAYER OF OAK-PINE FORESTS IN MIOST FAIRLY FERTILE SITES WITHIN ZHYTOMYR POLISSYA - Оrlov, О. О.; Zhukovskiy, О. V.; Zborovska, О. V.; Shevchuk, V. V.; Levkivskiy, О. V. (Forestry and Forest Melioration, 2018)
Introduction Grass–dwarf-shrub layer in wet fairly fertile sites is the richest by plant species among edatopes in Polissya. It consists of berry species – Vaccinium myrtillus L., V. vitis-idaea L., Fragaria vesca L., Rubus saxatilis L.; medicinal species – Betonica officinalis L., Hypericum perforatum L., Origanum vulgare L., Digitalis grandiflora Mill., Achillea millefolium L.; forage grasses – Calamagrostis arundinacea (L.) Roth, Trifolium medium L., Poa pratensis L. etc. For that reason, it is an urgent task to analyse modern parameters of 137Cs accumulation in the aboveground phytomass of plant species which make this layer. The aim of the research was to thoroughly analyse the intensity of 137Cs accumulation by the aboveground phytomass of species in the grass-dwarf-shrub layer, and to do it within the regular, third stage of the multiyear radioecological monitoring on the permanent experimental plot (established in 1994). Materials and Methods The research was done in July, 2018, on permanent experimental plot laid down in compartment 49, subcompartment 16 in the Povchanske Forestry Unit of State Enterprise “Lugynske Forestry” in Zhytomyr Region, in conditions of moist fairly fertile site. We found out that the grass–dwarf-shrub layer had a projective cover of 50-70%. Convallaria majalis (20-25%) and Pteridium aquilinum (20-30%) dominated in it. At that, the permanent species were Polygonatum odoratum (Mill.) Druce, Betonica officinalis L., Potentilla alba L., Rubus saxatilis L. etc. Phytocenosis: Querceto-Pinetum pteridioso-convallarioso-variaherbosum. We calculated the average value of density of 137Cs ground deposition. It made 233.5 ± 13.61 kBq·m-2. In addition, the aboveground phytomass of 45 plant species was collected in triplicate. All samples were dried and homogenized. Furthermore, we used the SEG-001 “AKP-S” spectrum analyzer with scintillation detectors to measure the 137Cs specific activity. The relative error for measuring this parameter didn’t exceed 15%. We chose the transfer factor (TF) as an indicator of the intensity of 137Cs accumulation by plant phytomass from the soil; it had a generally accepted unit of measurement, namely m2·kg-1·10-3. Results We found out that in the data we collected, the average values of TF of 137Cs from the soil to the aboveground phytomass were from 0.18 ± 0.024 m2·kg-1·10-3 in Vaccinium myrtillus to 5.90±0.873 m2·kg-1·10-3 in Dryopteris filix-mas. Therefore, according to the average TF values, the plant species were divided into 9 homogeneous groups, however heterogeneous taxonomic. We discovered that representatives of the largest families distributed among different homogeneous groups on the permanent expeiomental plot that was determined by the depth of their root systems placing in the soil. Conclusion We came to the conclusion that species of the grass-dwarf-shrub layer in wet fairly fertile sites accumulate 137Cs with low intensity and, thus, belong to the groups of very weak and weak radionuclide accumulation. We discovered that from 2014 through 2018, the average values of TF of 137Сs from the soil to the aboveground phytomass continued to decrease in the majority of species. We also noted that the species order in the ranked row changed according to the average TF values. 1 Fig., 4 Tables, 16 Refs.